Given: -2y + 5z = -3 <span>(first equation) </span>y = -5x - 4z - 5 (second equation) x = 4z + 4 <span>(third equation)<span> </span></span> Solution: PART 1 Substitute x with (4z + 4) in the second equation y = -5x - 4z - 5 y = -5(4z + 4) - 4z - 5
Then simplify y = -20z - 20 - 4z - 5
add like terms y = -20z - 4z - 20 - 5 y = -24z - 25
PART 2 : Find the value of z We got y is equal to (-24z - 25). Substitute y with (-24z - 25) in the first equation, and we'll find the value of z. -2y + 5z = -3 -2(-24z - 25) + 5z = -3 48z + 50 + 5z = -3
add like terms 48z + 5z = -3 - 50 53z = -53 z = -53/53 z = -1
The value of z is equal to -1
PART 3: Find y and x Find the value of y by substitution of -1 in the place of z. y = -24z - 25 y = -24(-1) - 25 y = 24 - 25 y = -1 The value of y is equal to -1
Find the value of x by substitution of -1 in the place of z. x = 4z + 4 x = 4(-1) + 4 x = -4 + 4 x = 0 The value of x is equal to 0